Reading of urban narrative in school: a contagion, interiorization and construction of social representations - Alfonso Talero, Óscar Emilio (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2020)
This article offers an analysis of the role of the reader and the reading processes (“Reception aesthetics”), literary literacy and reading didactics inside the classroom. Thus, beyond “formalize the literature” or “pedagogizing it”, it is about turning education into an understanding of urban narrative, where it is not taught, it is shared; it is not learned, it is internalized; it is not evaluated, it is expressed from the social representations produced by and in the students.